Influence of the Beam Size Radiation on the Depth Dose by Using 60Co - Kadhim, A.; Essa, S. (Iraqi Journal of Science, 2023)
Radiotherapy is medical use of ionizing radiation, and commonly applied to thecancerous tumor because of its ability to control cell growth.The amount of radiation used in photon radiation therapy called dose (measuredin grey unit), which depend on the type and stage of cancer being treated.In our work, we studied the dose distribution given to the tumor at differentdepths (zero-20 cm) treated with different field size (4×4- 23×23 cm).Results show that the deeper treated area has less dose rate at the same beamquality and quantity. Also it has been noted increasing in the field increasing in thedepth dose at the same depth even if the radiation energy is constant. Increasing inradiation dose attributed to the scattered radiation, which is expected,proportionately with increase in the beam size. The aim of work studies therelationship between the depth dose and the radiation source beam size